2018
DOI: 10.1111/jnc.14607
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drug transporters contributing to oxaliplatin‐induced peripheral neuropathy

Abstract: Oxaliplatin is widely used as a key drug in the treatment of colorectal cancer. However, its administration is associated with the dose-limiting adverse effect, peripheral neuropathy. Platinum accumulation in the dorsal root ganglion (DRG) is the major mechanism responsible for oxaliplatin-induced neuropathy. Some drug transporters have been identified as platinum complex transporters in kidney or tumor cells, but not yet in DRG. In the present study, we investigated oxaliplatin transporters and their contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 63 publications
0
46
1
Order By: Relevance
“…In contrast with our current findings, it was previously suggested that the transporter OCTN1 is a possible determinant of OIPN (6,12,20). Because of the expression of OCTN1 on the mitochondria, the neuroprotective effects of ergothioneine, an OCTN1-specific substrate, may be in part due to the contribution of intrinsic antioxidant activity to mitochondrial dysfunction rather than inhibition of oxaliplatin transport into DRGs.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with our current findings, it was previously suggested that the transporter OCTN1 is a possible determinant of OIPN (6,12,20). Because of the expression of OCTN1 on the mitochondria, the neuroprotective effects of ergothioneine, an OCTN1-specific substrate, may be in part due to the contribution of intrinsic antioxidant activity to mitochondrial dysfunction rather than inhibition of oxaliplatin transport into DRGs.…”
Section: Resultscontrasting
confidence: 99%
“…Although OIPN was still observed in patients receiving this combination, it is important to point out that the applied dasatinib dosing schedule was not opti- (22), in line with our toxicity evaluations using the same mouse model ( Figure 1B and Supplemental Figure 6A). Interestingly, some studies have also suggested that oxaliplatin is a transported substrate of the carnitine transporter OCTN2; however, the significance of this observation is unclear because administration of an OCTN2 substrate, L-carnitine, does not afford tissue protection against oxaliplatin (12,20). Furthermore, we found that dasatinib does not inhibit these transport mechanisms (Supplemental Figure 6, B and C).…”
Section: Resultsmentioning
confidence: 58%
“…These proteins are responsible for transporting oxaliplatin and are regarded as key transporters maintaining the intracellular concentration of platinum derivatives via active uptake and efflux processes. OCTN1 and OCTN2 are also functionally expressed within dorsal root ganglia neurons, and OCTN1 is thought to be the main contributor to the neuronal accumulation of oxaliplatin and a mediator of its neurotoxicity [4,[6][7][8]. In addition, CTR1 (copper transporter 1), CTR2 (copper transporter 2), ATP7A (copper-transporting p-type adenosine triphosphatase 1) and ATP7B (coppertransporting p-type adenosine triphosphatase 2) are copper transporters that not only maintain homeostasis and copper metabolism but also are involved in cisplatin, carboplatin and oxaliplatin transport.…”
Section: Oxaliplatin As a Neurotoxic Drugmentioning
confidence: 99%
“…Other interesting platinum‐based peripheral neurotoxicity pathways being explored are in early stages of development. One pathway focuses on cellular transport of platinum‐based compounds and aims to perform genetic or pharmacological knockout of transporters localized to the DRG in mice, such as OATP1B2 (OATP1B1 in humans), organic cation transporter novel type (OCTN2) protects against CIPN associated with and platinum‐based drugs . A second molecule of interest is apyrimidinic endonuclease/redox effector factor‐1 (APE1), which can be pharmacologically induced to increase DNA base excision repair, while simultaneously showing anticancer effects .…”
Section: Prevention Of Pipn: Clinical Trial Strategiesmentioning
confidence: 99%